The Moth-Flame Optimization Algorithm for Flow Shop Scheduling Problem with Travel Time - Ikhlasul Amallynda; Bhisma Hutama (Department Industrial Engineering, University of Muhammadiyah Malang, 2021)
This article examined the flow shop scheduling problem by considering the travel time between machines. The objective function of this problem was to provide a makespan. The Moth Flame Optimization (MFO) algorithm was proposed to solve the flow shop problem. The MFO experiment was carried out with a combination of iteration parameters and the population of the MFO algorithm to solve the flow shop scheduling problem. The computational results showed that MFO could produce a better solution than the actual scheduling method. Furthermore, the MFO Proposal Algorithm was able to reduce the makespan by up to 3%.